EDUKASI PEMANFAATAN KANDUNGAN PROTEIN IKAN LELE SEBAGAI UPAYA PENCEGAHAN STUNTING PADA IBU HAMIL DI DESA GARAHAN - Wahidah, Nur; Jannah, Nur; Puspita W., Dhevin MQ Agus; Ismaniya, Fais Zhatul (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
Stunting is a significant public health issue in Indonesia, particularly among pregnant women and children. Based on the data from the village posyandu in Garahan in 2024, the number of Stunting cases in Garahan Village reached 13 children. This research aims to provide education on the utilization of catfish protein content as a strategy to prevent Stunting in pregnant women in Garahan Village. Catfish is chosen because of its high protein content and its relatively easy availability in local communities, especially in Garahan Village. The method used in this research is educating the utilization of catfish protein as a nutritional option for preventing Stunting in pregnant women. This education also aims to provide in-depth knowledge about Stunting and to equip PKK cadres and the residents of Garhan village with new skills. In addition, there has been a decrease in the incidence of Stunting in infants born to mothers who regularly consume catfish. This finding indicates that the utilization of catfish as a source of protein can be an effective strategy in preventing Stunting among pregnant women in rural areas. This research suggests the need for the implementation of educational programs and subsidies to improve the accessibility of catfish among pregnant women as part of efforts to prevent Stunting.